Effects of music on repeated-sprint performance of elite tunisian soccer players: comparing morning to afternoon practice sessions - Tounsi, M.; Aloui, A.; Messaoud, S.; Chtourou, H.; Trabelsi, Y. (Perceptual and Motor Skills, 2024)
Our aim in the present study was to examine the effect of listening to self-selected music during soccer warm-ups in morning and afternoon sessions on repeated-sprint performances of elite soccer players. Twenty elite academy male soccer players performed a repeated-sprint ability (RSA) test in the morning (i.e., 07:00 hours) and in the afternoon (i.e., 17:00 hours), with or without listening to music during the warm-up period. The RSA test consisted of six 40-meter sprints with 180° direction changes interspersed with a 20-second passive recovery period. Ratings of perceived exertion (RPE) were obtained at the end of the warm-up period and immediately after the RSA test. Results showed that listening to music during warming-up had no significant effect on these selected performance measures (i.e., mean sprint time, best sprint time, RSA decrement), regardless of whether performances were in the morning or the afternoon. Moreover, players reported higher post-warm-up RPE scores in the music listening condition than in the no-music listening condition, only in the afternoon session. Furthermore, RPE scores measured after the RSA test were higher in the no-music listening condition compared to the music listening condition, only in the morning session. Thus, the use of music during warming-up in elite soccer players appears to be an individual athlete`s choice but not a reliable means of enhancing performance.